Biosynthesized silver nanoparticles for electrochemical detection of bromocresol green in river water - Moustafa Zahran; Amr Mohamed Beltagi; Mahmoud Rabie; Reham Maher; Abla Ahmed Hathoot; Magdi Abdel Azzem (Royal Society Open Science, 2023)
In this study, silver nanoparticles (AgNPs)-based electrochemical sensor has been reported for assessing bromocresol green (BG) in river water. Firstly, AgNPs were greenly produced using the aqueous extract of Ficus sycomorus leaves. Then, the AgNP-modified glassy carbon (GC) electrode was prepared using the sticking method. AgNPs were characterized using transmission electron microscope (TEM), X-ray diffraction (XRD), square wave voltammetry (SWV) and scanning electron microscope (SEM). TEM and SEM were used for determining the size of AgNPs before and after adsorption, respectively. The results show that there was an increase in AgNP size from 20 to 30 nm. Additionally, XRD was used for characterizing the crystal nature of AgNPs, while SWV exhibited a characteristic oxidation peak of AgNPs at 0.06 V. Moreover, cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) were used for characterizing the catalytic effect of AgNPs. BG as a targeted pollutant was detected at AgNPs/GC based on its oxidation through proton and electron transfer. Two peaks corresponding to the monomer and polymer oxidation were detected. The monomer- and polymer-based sensors have revealed a linear range of 2.9 × 10−5 to 2.1 × 10−4 mole l−1 and low detection limits (LODs) of 1.5 × 10−5 and 1.3 × 10−5 mole l−1, respectively.